Features of adhesives on base of vinylaromatic thermoplastic elastomers - L. R. Lusova; T. N. Dorokhova (Тонкие химические технологии, 2011)
Research of adhesive and strength properties of vinylaromatic thermoplastic elastomers presented at the russian market show significant differences between them. That due not only different chemical nature of block copolymers, but also differences in their structural parameters.